Implementasi perhitungan harga pokok produksi tahu sumedang dengan penerapan metode full costing dan variable costing - Juantara, Billy Akbar; Kusumastuti, Ratih; Tiswiyanti, Wiwik (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This research was conducted to determine the calculation of the cost of goods manufactured according to the company, to determine the calculation of the cost of production when using the full costing method and to determine the comparison of these methods. The location of the research is tofu company located in Pematang Sulur Jambi City. In regard to the cost of production, the company uses its own method which is certainly notappropriate in its implementation. Therefore an appropriate method is needed so that in calculating the cost of production is more accurate and the company can be more precise in making decisions. Based on this, a problem arises that is how the analysis of determining the method of calculating the cost of production on the tofu company if you use the full costing and variable costing method. The results of the study indicate that the full costing method can provide an accurate calculation of HPP, which in its calculation includes all elements of costs, both raw material costs, direct labor costs and fixed variable BOP. This is because the full costing method is very suitable for long-term decision making.